(untitled) (Bangladesh Journal of Zoology, 2018)
A cross-sectional study was conducted to know the occurrence of common diseases in staff and their family members in three residential halls of University of Dhaka. The individuals were interviewed about the diseases they encountered recently. Among 270 respondents, the highest occurrence of diarrhea (44.44%) was recorded among 16-30 years old staff of Dr. Muhammad Shahidullah hall. Peak occurrence of sinusitis (37.25%) was observed among the staff aged 31-45 years old of the same hall. The highest occurrence of eczema (37.5%) was observed among the staff aged 46-60 years old of Amar Ekushey hall. Diarrhoea was prevalent among the groups who preferred food from hotel comprising the highest prevalence (72.73%) in Dr. Muhammad Shahidullah hall (p = 5.024). The uppermost occurrence of jaundice was recorded among the staff of Fazlul Huq Muslim hall who used to take food from outside hotels (71.43%). Bangladesh J. Zool. 46(1): 45-52, 2018